A Study on Development of IoT Software Vulnerability (Using Fake Information) Response System based on Artificial Intelligence - Mook KANG, Jang; Hee YOON, Choel; SHIN, Jiho (International Journal of Engineering and Technology, 2018)
The use of IoT devices such as wearable digital devices based on mobile devices is increasingly evident. In IoT-based environment, communication protocol of IoT category and lightweight special environment software are used instead of universal network configuration. Due to the operating structure of IoT, preparation of countermeasures to automatically analyze IoT software vulnerabilities based on artificial intelligence should be considered. Because of the rapid growth of IoT equipment and the expectation that there will be a sharp increase in the need to identify facts about vulnerabilities and improper use associated with IoT services naturally. It is necessary to apply artificial intelligence technology for classification and automatic collection and analysis of IoT vulnerabilities for wearable devices and smart home devices through artificial intelligence analysis technology. Sequentially, To acquire the data from the device, internal data and network data of the specified device after searching the protocol of the IoT device, it is possible to cope with IoT software vulnerability applying AI intelligence analysis method to related data. In this paper, we investigate software vulnerabilities in IoT environment and propose a technique to cope with ioT vulnerabilities through artificial intelligence.Â